Factors influencing a potato farmer's choice of seed supplier: Empirical evidence from the Philippines - Batt, Peter (Taylor & Francis, 2001)
Empirical evidence collected from comprehensive personal interviews with potato farmers in The Philippines reveals five factors that best explain a farmer's choice of seed supplier. Seed quality and the seed supplier's reputation are the two most important factors. Given the high cost of seed and the impact seed quality has not only on the current crop but any future crops derived from that seed, such is not unexpected. Results suggest that by providing technical support, enhancing offer quality and facilitating regular communication, it is possible for a proximal seed supplier to differentiate their product offer from alternative suppliers. Fortuitously, such investments are most appreciated by the larger potato farmers.